School groups in Rio Grande do Norte: mapping studies about primary school - Cruz, Paula Lorena Cavalcante Albano da (Revista Hipótese, 2019)
Article deals with a quantitative and qualitative analysis of dissertations and theses, published between 2005 and 2018 by UFRN, which deal with theme of the North-Rio Grande school groups. We intend to understand how they collaborated to build a historiography of these public educational institutions of Rio Grande do Norte. In order to understand our goal we seek to work with content analysis. In the midst of the results achieved, observed that the academic productions in general sought to collaborate in the construction of the history of the state’s educational institutions, as well as in the knowledge of education in the State.